2023
DOI: 10.1097/tp.0000000000004545
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Red Blood Cell Transfusion and Primary Graft Dysfunction After Lung Transplantation

Abstract: Background. In this international, multicenter study of patients undergoing lung transplantation (LT), we explored the association between the amount of intraoperative packed red blood cell (PRBC) transfusion and occurrence of primary graft dysfunction (PGD) and associated outcomes. Methods. The Extracorporeal Life Support in LT Registry includes data on LT recipients from 9 high-volume (>40 transplants/y) transplant centers (2 from Europe, 7 from the United States). Adult patients who underwent bilateral or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Several clinical, transplant, and donor characteristics differed significantly among PMV patients. This group received more red cell transfusions during surgery, associated with a higher risk of PGD [ 38 , 39 ]. In addition, higher mean pulmonary artery pressures and a diagnosis of pulmonary arterial hypertension, well-known risk factors for left ventricular dysfunction following lung transplantation [ 38 , 40 ], as well as a greater proportion of recipients receiving intraoperative ECMO may indicate more severe pulmonary edema, which adversely affects early graft function and delays ventilator weaning and time to extubation [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical, transplant, and donor characteristics differed significantly among PMV patients. This group received more red cell transfusions during surgery, associated with a higher risk of PGD [ 38 , 39 ]. In addition, higher mean pulmonary artery pressures and a diagnosis of pulmonary arterial hypertension, well-known risk factors for left ventricular dysfunction following lung transplantation [ 38 , 40 ], as well as a greater proportion of recipients receiving intraoperative ECMO may indicate more severe pulmonary edema, which adversely affects early graft function and delays ventilator weaning and time to extubation [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most compelling evidence linking intraoperative transfusion to primary graft dysfunction was published by the multicenter Lung Transplant Outcomes Group (N = 1,255), 12 suggesting that large-volume transfusion of red cells (more than 1 l) and platelets during lung transplantation is independently associated with early graft dysfunction. 11,14 In one multicenter study of 729 registry patients that bled during lung transplantation, those receiving more than 4 units intraoperatively were 2.2 times more likely to have severe allograft injury within 72 h. 15 Seay et al 16 examined transfusion strategies for lung transplantation and identified that patients receiving an increased plasma-to-erythrocyte unit ratio had an associated greater degree of primary graft dysfunction, although patients with increased ratios in this cohort also received a higher total transfusion volume.…”
Section: The Problem: Transfusion and Related Outcomes In Lung Transp...mentioning
confidence: 99%